DEVELOPMENT OF ICT-BASED LEARNING MEDIA ON FIQH MATERIAL CHAPTER TAYAMUM for 1st GRADE MADRASAH IBTIDAIYAH - Syari’ah, Atiris; Haidar, Putri Bayu; Nabilah, Nafa (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2024)
Learning media is one of the main factors supporting the achievement of learning goals. Information and Communication Technology-based learning Media is relevant to the current education era, making it easier for educators to create and develop various learning media that attract students. The author used Canva Presentation as an ICT-based learning media for the Tayamum chapter of Fiqh material for 1 st grade Madrasah Ibtidaiyah. This paper uses a research and development approach using the ASSURE model with development steps: (1) Analyze the learner, (2) state standards and objectives, (3) select the strategic, technology, media, and materials, (4) utilize technology, media and materials, (5) require learner participation, (6) evaluate and revise. The results obtained are ICT-based learning media created using Canva and developed with the ASSURE model, suitable to be implemented on Fiqh material, especially in the Tayamum chapter for 1 st grade Madrasah Ibtidaiyah.